Peningkatan keterampilan mengomunikasikan hasil karya pantun melalui model pembelajaran gallery walk pada peserta didik kelas V sekolah dasar - Yusfita Asmarandani; Retno Winarni; Muhammad Ismail Sriyanto (Universitas Sebelas Maret, 2020)
The research aims to improve the skill of communicating poetry results using gallery walk model. This research is a classroom action research with two cycles. The subject in this research is fifth grades of primary school Bumi 1 Surakarta in the 2019/2020 academic year, totaling 21 students. The data collection technique used in this research is interviews, observations, test and documentaries. The technique for data analysis used is the interactive analysis Miles and Huberman. The first cycles at the first meeting of the class average is 80,95 with the 60,90 % classification. The second cycles at the second meeting experienced significant increase. The conclusion of the meeting was 85,71 % and the class average of 86,90. The research concludes that use of the gallery walk model may improve the communication skill of the poetry results on 5th grade of primary school Bumi 1 Surakarta in the 2019/2020 academic year.